Decision making in fencing training and its relationship with reaction time - Ó Martínez de Quel; E. López; M. Sillero; F. Saucedo (Federación Extremeña de Balonmano; University of Extremadura, 2011)
In fencing, certain tasks are designed to develop the mechanism of perception, decision and/ or execution. One way to know the effect to one or another is to measure the Reaction Time, making inferences about the effect of the manipulated variables in the research about the mechanisms. On the other hand, Reaction Time can help us to determine the level of perceptual ability and decision making of a fencer. The objectives of this study were, test the differences in perception and decision making depending on the weapon, and determine what actions are more difficult to perception and decision making in fencing. The subjects were 18 members of the spanish national fencing team. Fencers were placed facing a screen in which videos were projecting appearing the coach of each weapon launching actions to which the fencers had to react quickly. The results showed significant differences between the epeeists and the foil and sabre fencers. On the other hand, it was found more time is required to make the decision is to distinguish if the opponent´s attack had a good or bad execution. Key words: Combat Sports, Fencing, Decision Making, Reaction Time